Assertive Student Victims of Domestic Violence: Basic Qualitative Analysis From Guidance and Counseling Perspective - Afdal, Afdal; Meynia, Adhilla; Rahmawati, Dini Fitriani; FIkri, Miftahul; Syapitri, Denia; Hariko, Rezki (Indigenous, 2022)
Abstract. Domestic Violence is mostly experienced by women and children. Victims of domestic violence will be moody, quiet, aggressive, and tend to have less assertive behavior. Assertive behavior is the ability to convey what you want, feel, and think to others openly and honestly without intending to offend. This study aims to determine the description of assertive behavior in child victims of domestic violence. The study was conducted on 4 student victims of domestic violence (4 girls; aged 17-19 years; student status, students, and private employees) through observation and interviews with data reduction analysis, data presentation, and conclusion drawing. The results showed that the assertive behavior of children, as the victims of domestic violence, was equally low indicated by the request to convey rights, rejection of invitations, self-expression, giving praise to people, and taking part in the conversation. The difference, however, is found in the aspect of rejection, subjects DFS, IR, P are better than subject C. To increase assertive behavior in children who are victims of domestic violence, an exercise to communicate assertively at home for children and parents is needed so that children and parents can improve their ability to control emotions, hence minimizing the mistreatment of children. Therefore, the role of Guidance and Counseling is very much needed through information services and content mastery. The material that can be given is the application of assertiveness on daily basis to children as victims of domestic violence.Keywords: assertive; children victims of domestic violence; perspective of guidance and counseling.